2021
DOI: 10.21203/rs.3.rs-399869/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PRM-MS Quantitative Analysis of Isomeric N-Glycopeptides Derived From Human Serum Haptoglobin of Patients With Cirrhosis and Hepatocellular Carcinoma

Abstract: Currently surveillance strategies have inadequate performance for the early detection of hepatocellular carcinoma (HCC). Protein glycosylation is a potential source of biomarkers to differentiate between cirrhosis and HCC. We performed a comprehensive LC-PRM-MS approach where a targeted parallel reaction monitoring (PRM) strategy was coupled to a powerful LC system to study the microheterogeneity of haptoglobin (Hp) extracted from 15 patients with cirrhosis and 15 with HCC. We found that our strategy was able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Whereas advanced fragmentation techniques such as high energy collision dissociation (HCD), electron transfer/higher‐energy collision dissociation (EThcD), electron‐detachment dissociation (EDD), infrared multiphoton dissociation (IRMPD), and UV‐photon dissociation (UVPD) can provide sufficient fragment ions, and therefore structural information of large molecules as are glycopeptides (Depraz Depland et al, 2018; Myers et al, 2013, Riley & Coon, 2018; Zhurov et al, 2013). Besides, targeted‐MS n modes such as MRM and PRM provide an increase in specificity and sensitivity that can be extrapolated to accurate quantitation methods of isomeric glycan and glycopeptides (Zhou et al, 2015; Reyes et al, 2021).…”
Section: Ms‐based Isomeric Characterization Of Glycans and Glycopeptidesmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas advanced fragmentation techniques such as high energy collision dissociation (HCD), electron transfer/higher‐energy collision dissociation (EThcD), electron‐detachment dissociation (EDD), infrared multiphoton dissociation (IRMPD), and UV‐photon dissociation (UVPD) can provide sufficient fragment ions, and therefore structural information of large molecules as are glycopeptides (Depraz Depland et al, 2018; Myers et al, 2013, Riley & Coon, 2018; Zhurov et al, 2013). Besides, targeted‐MS n modes such as MRM and PRM provide an increase in specificity and sensitivity that can be extrapolated to accurate quantitation methods of isomeric glycan and glycopeptides (Zhou et al, 2015; Reyes et al, 2021).…”
Section: Ms‐based Isomeric Characterization Of Glycans and Glycopeptidesmentioning
confidence: 99%
“…Gutierrez Reyes et al recently reported a comprehensive LC‐PRM‐MS approach where a targeted parallel reaction monitoring (PRM) strategy was used for the quantitation of isomeric haptoglobin N ‐glycopeptides derived from cirrhosis and hepatocellular carcinoma (HCC) samples (Reyes et al, 2021). The target glycopeptides were acquired and fragmented by HCD with a collision energy of 25%.…”
Section: Ms‐based Isomeric Characterization Of Glycans and Glycopeptidesmentioning
confidence: 99%
See 3 more Smart Citations